2011
DOI: 10.1142/s0219519411004149
|View full text |Cite
|
Sign up to set email alerts
|

Friction of Stainless Steel, Nickel-Titanium Alloy, and Beta-Titanium Alloy Archwires in Two Commonly Used Orthodontic Brackets

Abstract: In orthodontic treatment, the efficiency of tooth movement is affected by the frictional force between the archwire and bracket slot. This study evaluated the static and kinetic frictional forces produced in different combinations of orthodontic archwires and brackets. Three types of archwires [stainless steel, nickel-titanium (NiTi) alloy, and betatitanium (TMA) alloy] and two types of brackets (stainless steel and self-ligating) were tested. Both static and kinetic frictional forces of each archwire-bracket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Each of the archwire-bracket combinations has a unique set of physical properties that affect its performance [81]. Frictional force in the archwire-bracket slot combination affects tooth movement [75]. To simulate the load of the wire in service with values in range from 0.196 to 0.98 N, the normal load during experiments should be around 1 N [5].…”
Section: Tribocorrosion and Wear Properties Of Niti Alloymentioning
confidence: 99%
“…Each of the archwire-bracket combinations has a unique set of physical properties that affect its performance [81]. Frictional force in the archwire-bracket slot combination affects tooth movement [75]. To simulate the load of the wire in service with values in range from 0.196 to 0.98 N, the normal load during experiments should be around 1 N [5].…”
Section: Tribocorrosion and Wear Properties Of Niti Alloymentioning
confidence: 99%
“…However, it is challenging to determine the actual force because 12-60% of the total force is lost to sliding resistance 2) . Factors of sliding resistance include the materials for the brackets and arch wires 3,4) , surface roughness, sizes of the arch wires 5,6) , angulation and torque between the bracket-arch wire combination, distance between brackets, types of ligations, and the oral environment. When one surface slides over another surface, plastic deformation occurs at the asperities or at the peak of surface irregularities between the two objects, leading to movement resistance due to friction.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has a high friction coefficient, is brittle, and traumatizes the enamel during bracket removal [10][11][12] . To reduce friction and overall treatment duration, a self-ligating bracket was developed 4,13,14) . However, several studies showed varying results such as an inability to conclude whether these brackets significantly reduce friction and treatment duration 4,15,16) .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of frictional resistance of orthodontic wires, TiMo wires generated the highest friction values, followed by NiTi and SS wire, when using the SS brackets [ 16 ]. Another study stated that SS wires performed the least amount of friction, followed by CoCr, NiTi, and β-Ti wires [ 17 ].…”
Section: Introductionmentioning
confidence: 99%